Characterizing the sprint threshold (25.2 km/h): a case study analysis on how soccer players reach sprint speeds and what relative intensity the threshold represents - Silva, H.; Nakamura, F. Y.; Mendez-Villanueva, A.; Gomez-Diaz, A.; Menezes, P.; Marcelino, R. (Sport Sciences for Health, 2024)
Purpose This study investigated how soccer players reach sprint speeds (> 25.2 km·h-1) and what that fixed threshold represents to each player regarding their individual match peak speeds registered during competition.